China : fragile superpower - Shirk, Susan L. (Oxford ; New York : Oxford University Press, 2007)
"Once a sleeping giant, China today is the world's fastest growing economy -- the leading manufacturer of cell phones, laptop computers, and digital cameras -- a dramatic turn-around that alarms many Westerners. But In China: Fragile Superpower, Susan L. Shirk opens up the black box of Chinese politics and finds that the real danger lies not in China's astonishing growth, but in the deep insecurity of its leaders. China's rulers face a troubling paradox: the more developed and prosperous the country becomes, the more insecure and threatened they feel. Unless we understand China's brittle internal politics and the insecurities of its leaders, we face the very real possibility of unavoidable conflict with rising China. This book provides that understanding"--Jacket
Strong abroad but fragile at home -- China's economic miracle -- Domestic threats -- The echo chamber of nationalism : media and the Internet -- The responsible power -- Japan : "when the Chinese people get angry, the result is always big trouble" -- Taiwan : "a question of regime survival" -- The United States : "external troubles can become internal troubles" -- China's weakness, America's danger.
"How China's internal politics could derail its peaceful rise"--Jacket
Includes bibliographical references (pages 273-310) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Nationalism -- China; China -- Politics and government -- 2002-; Nationalisme -- Chine; POLITICAL SCIENCE -- Political Process -- General; Nationalism; Politics and government; China; Kina -- politik och förvaltning.; Kina -- internationella relationer -- 2000-talet.; media -- information technology -- public opinion -- China; China -- foreign policy -- internal politics -- government -- nationalism; Nationalism -- China; China -- Politics and government -- 2002-; Since 2002